Paradiplomacia ambiental e econômica no regime internacional de mudanças climáticas : a iniciativa regions adapt - Pinho, Mariângela Mendes Lomba (2017)
Although the International Climate Change Regime has been growing to higher proportions day after day, problems related to global warming seem to have been causing successive losses to mankind; Several initiatives, however, have been implemented towards the mitigation of climate hazards. There is need to go beyond that, though, and take adapting actions to current and future conditions to ensure sustainable development. The State has evidenced its lack of conditions to act efficiently in that segment and that said space is being slowly occupied by subnational players, who become important agents in the international relations. In that context, and considering the capitalist economies in a globalized environment, this thesis analyzes the environmental and economic paradiplomacy as a governance tool to contribute with more effective results, using soft law tools and acting in transnational climate networks, which by means of environmental economic instruments enable project financing. If the adapt is a new path taken in climate-related discussions, an innovative initiative, called Regions Adapt, still in the structuring phase, presents a bold proposal for subnational players. To achieve the outlined goals, this research was initially composed of the bibliographic and documentary method, with a review of the scholarly literature on the topic in general, since specific scientific works have not been found, complemented by technical visits and open interviews. Afterwards, the works was developed on a single case study to test the research compilations. Under such standpoint, São Paulo State was selected, once it holds the economic leadership in the country and because it is the region where this doctoral program is inserted, in addition to the vast experience in several actions already implemented in the international agenda of sustainability. Results indicate that the environmental paradiplomacy and economic paradiplomacy are indispensable tools to help face climate change and foment the new concept of economy, with an array of environmental economic instruments being offered in the market, although, in practical terms, access to the resources is still complex. Researches evidenced that due to the recent installation of the Regions Adapt initiative, economic aspects are not yet outlined. As to the State of São Paulo, object of the single case study, nowadays, despite the difficulties, it presents itself as a pioneer in environmental and paradiplomacy matters.